UPAYA MENINGKATKAN KEAKTIFAN BELAJAR SISWA DENGAN MODEL PEMBELAJARAN FLIPPED CLASSROOM PADA PEMBELAJARAN PENDIDIKAN PANCASILA KELAS V SEKOLAH DASAR - Darmawan, Raditya Rizky; Nina Nurhasanah; Edwita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This classroom action research aims to improve students’ active learning in fifth grade of SDN Menteng Atas 14 by implementing the flipped classroom learning model. The subjects of this study were 24 students of Class V-B. The research was conducted from April to June 2025, during the second semester of the 2024/2025 academic year. The research was carried out in 2 cycles. The method used was Classroom Action Research (CAR) with the Kemmis & McTaggart model, consisting of four stages: planning, implementation, observation, and reflection. The results of the study showed an increase in students’ active learning from 69.6% in Cycle I to 91.7% in Cycle II. The implementation of the flipped classroom model also increased from 90% in Cycle I to 98% in Cycle II. It can be concluded from the data analysis that the use of the flipped classroom model can effectively improve the active learning of Class V-B students of SDN Menteng Atas 14 in Pancasila Education lessons.